Improving Early Grade Reading Outcomes: Aprender a Ler in Mozambique. Issue 155 (March 2017) - Burchfield, Shirley; Hua, Haiyan; Noyes, David; van de Waal, Willem
Abstract: The Government of Mozambique has long struggled to improve the low reading levels of children in early grades. With funding from the U.S. Agency for International Development (USAID) in 2012, World Education collaborated with the Ministry of Education and Human Development (MINEDH) to improve reading by developing a research‐based reading intervention and testing it in two provinces. This article examines student reading performance from cohorts of second and third graders before and after a 1‐year intervention compared to that of a control group and identifies factors required for successful scale‐up.